Literackie przekłady i formy prezentacji twórczości Olgi Tokarczuk w Chinach - Lan, Wu (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The article chronologically reconstructs the process of reception of Olga Tokarczuk’s prose in China with particular focus on the period after she received the Nobel Prize for Literature. The author invokes utterances of the translators, publishers and critics to demonstrate how Tokarczuk’s works fare on the Chinese book market in terms of marketing, in the context of sales results and their presence online, which elements of her writings are closest to the Chinese readers and why, what global literary and cultural discourses her work is assigned to and what challenges the Chinese translators are faced with when translating her prose.